Neutrosophic Vague Generalized Pre-Closed Sets in Neutrosophic Vague Topological Spaces - A. Mary Margaret; M. Trinita Pricilla (International Journal of Mathematics And its Applications, 2017)
The aim of this paper is to introduce and develop a new class of sets namely neutrosophic vague generalized pre-closed sets in neutrosophic vague topological space. Further we have analyse the properties of neutrosophic vague generalized pre-open sets. Also some applications namely neutrosophic vague $ T_{1/2} $ space, neutrosophic vague $ {}_{p}T_{1/2} $ space and neutrosophic vague $ {}_{gp}T_{1/2} $ space are introduced.